Pharmaceutical compounding and dispensing - Langley, Christopher Andrew; Belcher, Dawn. (London ; Philadelphia : Pharmaceutical Press, 2012)
"This FASTtrack book has been designed to assist the student compounder in understanding the key dosage forms encountered within extemporaneous dispensing."--Publisher.
1. Introduction -- 2. Solutions -- 3. Suspensions -- 4. Emulsions -- 5. Creams -- 6. Ointments, pastes and gels -- 7. Suppositories and pessaries -- 8. Powders and capsules -- Answers to self-assessment -- Appendix 1. Glossary of terms in formulations -- Appendix 2. Abbreviations commonly used within pharmacy -- Appendix 3. Formulae contents.
Includes bibliographical references (pages 199-201) and index.
Keywords: Drugs -- Dosage forms -- Examination, questions, etc; Drugs -- Dosage forms; Medicine -- Formulae, receipts, prescriptions; Pharmacy; Drug Compounding -- Examination Questions; Dosage Forms -- Examination Questions; Drug Prescriptions; Pharmaceutical Preparations